Framing the private land conservation conversation: Strategic framing of the benefits of conservation participation could increase landholder engagement. Issue 61 (July 2016) - Kusmanoff, Alexander M.; Hardy, Mathew J.; Fidler, Fiona; Maffey, Georgina; Raymond, Christopher; Reed, M.S.; Fitzsimons, James A.; Bekessy, Sarah A.
Highlights: We use a value orientation framework to analyse how the participation benefits of Australian private land conservation (PLC) schemes are framed. We find that messages are biased towards promoting environmental benefits compared to landholder and social benefits. This includes market-based schemes that seek to appeal to production-focussed landholders and those not already involved in conservation. We argue that framing the benefits of PLC more broadly would engage a greater diversity of landholders, aiding PLC recruitment. Abstract: How conservation messages are framed will impact the success of our efforts to engage people in conservation action. This is highly relevant in the private land conservation (PLC) sector given the low participation rates of landholders. Using a case study of PLC schemes targeted at Australian landholders, we present the first systematic analysis of communication strategies used by organisations and government departments delivering those schemes to engage the public. We develop a novel approach for analysing the framing of conservation messages that codes the stated benefits of schemes according to value orientation. We categorised the benefits as flowing to either the landholder, to society, or to the environment, corresponding to the egoistic, altruistic and biospheric value orientations that have been shown to influence human behaviour. We find that messages are biased towards environmental benefits. Surprisingly, this is the case even for market-based schemes that have the explicit objective of appealing to production-focussed landholders and those who are not already involved in conservation. The risk is that PLC schemes framed in this way will fail to engage more egoistically oriented landholders and are only likely to appeal to those likely to already be conservation-minded. By understanding the frame in which PLC benefits are communicated, we can begin to understand the types of people who may be engaged by these messages, and who may not be. Results suggest that the framing of the communications for many schemes could be broadened to appeal to a more diverse group (and thus ultimately to a larger group) of landholders.